Age-dependent changes in ultrastructure of the defensive glands of Neocapritermes taracua workers (Isoptera, Termitidae) - Šobotník, Jan (Ventricular Restraint Improves Outcomes in HF Patients with CRT, 2014)
Protection against predators and competitors is one of the main concerns of termite colonies, which developed a specialised defensive caste, the soldiers. However, soldiers are rare or even missing in several lineages of termites, while workers often develop new defence strategies especially in soil-feeding species. Here, we describe the morphology and ultrastructure of the autothysis-associated glands of Neocapritermes taracua workers and report their age-related changes in structure. The defensive glands of N. taracua workers consist of a pair of labial and a pair of crystal glands, whose secretions mix together through autothysis. Autothysis always occurs at the line of weakness connecting the anterior parts of the crystal-bearing pouches. The crystal glands consist of groups of bicellular secretory units (secretory and corresponding canal cells) which secrete the blue crystal material into external pouches. Their secretory activity is maximal in the middle of worker life, and is considerably lower in very young and old workers. The labial glands are composed of two types of secretory cells: the central and the parietal cells. While the central cells are developed similarly to other termites and secrete proteinaceous secretion into labial gland ducts, the parietal cells develop proteinaceous granules which may eventually bud off the cells. The secretory function of parietal cells is so far unique to N. taracua and differs from other termite species in which they are only responsible of water uptake by acini. The defensive device of N. taracua is truly exceptional as it involves a new gland and a previously undescribed function for parietal cells, being a remarkable example of evolution of morphological innovation.